The effects of systematically altered footwear features on biomechanics, injury, performance, and preference in runners of different skill level: a systematic review. (1st September 2020) - Hoitz, Fabian; Mohr, Maurice; Asmussen, Michael; Lam, Wing-Kai; Nigg, Sandro; Nigg, Benno
Abstract: Matching running footwear features to the functional needs of specific groups of runners stratified according to their training status or running experience has the potential to improve footwear preference, enhance running performance, and reduce the risk of running-related injuries. The complexity of modern running shoes in combination with the various functional needs of specific groups of runners, however, introduces many confounding factors, disguising what an appropriate shoe design should entail. As a result, it is crucial to identify and synthesise the effects of systematically modified running footwear features on lower extremity biomechanics, performance, injury risk, and footwear preference in runners of different skill levels to advance the knowledge of running biomechanics and footwear. The databases Scopus and PubMed were searched for related studies and 895 articles were identified. After the application of exclusion criteria, 68 articles remained and were arranged in a matrix that highlighted the investigated footwear feature and runner level. The effects of 20 footwear features on lower extremity biomechanics, injury, performance, and preference in novice, recreational, and high calibre runners were synthesised. Laced uppers with harder midsole materials in the forefoot/lateral regions of the shoe and softer materials in the rearfoot/medial regions increased comfort and thus likely preference. To increase performance, footwear should be constructed as lightweight as possible, and implement a range of different bending stiffness for individual needs. Injury risks at the knee joint were reduced in footwear with thinner midsoles. For high calibre runners, specifically, insoles should be custom moulded to the shape of the foot, and special attention needs to be payed to the elasticity of the upper, in order to avoid detrimental shifts in running patterns.